2016
DOI: 10.1093/mnras/stw951
|View full text |Cite
|
Sign up to set email alerts
|

Detection of emission lines fromz∼ 3 DLAs towards the QSO J2358+0149

Abstract: Using VLT/X-shooter we searched for emission line galaxies associated to four damped Lyman-α systems (DLAs) and one sub-DLA at 2.73 z 3.25 towards QSO J2358+0149. We detect [O III] emission from a "low-cool" DLA at z abs = 2.9791 (having log N(H I) = 21.69 ± 0.10, [Zn/H] = −1.83 ± 0.18) at an impact parameter of, ρ ∼ 12 kpc. The associated galaxy is compact with a dynamical mass of (1 − 6) × 10 9 M ⊙ , very high excitation Hβ] both greater than 10), 12+[O/H] 8.5 and moderate star formation rate (SFR 2 M ⊙ yr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 108 publications
4
29
1
Order By: Relevance
“…We derive the star-formation rate (SFR) of this candidate based on the Lyα flux (FLyα = 1.9 × 10 −17 erg s −1 cm −2 , that corresponds to the Lyα luminosity of LLyα = 7.7 × 10 41 erg s −1 ) using the Kennicutt (1998) relation. The derived SF R of 0.7 M⊙ yr −1 is a bit lower than other detection of DLA counterparts at z > 2 reported by some previous studies (e.g., Fumagalli et al 2010;Péroux et al 2012;Bouché et al 2013;Fynbo et al 2013;Krogager et al 2013;Srianand et al 2016). …”
Section: A Candidate Of a Dla Counterpartcontrasting
confidence: 67%
See 1 more Smart Citation
“…We derive the star-formation rate (SFR) of this candidate based on the Lyα flux (FLyα = 1.9 × 10 −17 erg s −1 cm −2 , that corresponds to the Lyα luminosity of LLyα = 7.7 × 10 41 erg s −1 ) using the Kennicutt (1998) relation. The derived SF R of 0.7 M⊙ yr −1 is a bit lower than other detection of DLA counterparts at z > 2 reported by some previous studies (e.g., Fumagalli et al 2010;Péroux et al 2012;Bouché et al 2013;Fynbo et al 2013;Krogager et al 2013;Srianand et al 2016). …”
Section: A Candidate Of a Dla Counterpartcontrasting
confidence: 67%
“…Since DLAs dominate the neutral-gas content in a wide redshift range (Storrie-Lombardi & Wolfe 2005), they are thought to be gas reservoirs for the starformation in the high-z Universe. Though the DLA is such an important population, their nature is still under the debate (e.g., Prochaska & Wolfe 1997;Taniguchi & Shioya 2000;2001;Kacprzak et al 2010) because it is often difficult to identify their optical counterparts due to their faintness, especially at high redshift (see for recent identifications at z > 2, Fynbo et al 2010;2011;Péroux et al 2011;Bouché et al 2013;Krogager et al 2012, Kashikawa et al 2014, Srianand et al 2016Sommer-Larsen & Fynbo 2017 and references therein). In many cases, counterparts of high-z DLAs have been found as LAEs.…”
Section: Introductionmentioning
confidence: 99%
“…Cen 2012;Bird et al 2014) or semi-analytical models (e.g. Berry et al 2016) but direct associations with galaxies remain difficult to establish, with only a few associations between intervening DLAs and galaxies revealed so far at z > 2 (Møller & Warren 1993;Møller et al 2004;Fynbo et al 2010;Krogager et al 2012;Noterdaeme et al 2012b;Bouché et al 2013;Kashikawa et al 2014;Hartoog et al 2015;Srianand et al 2016). Indeed, statistical studies show a low level of in-situ star formation (Rahmani et al 2010;Fumagalli et al 2015), although Ly-α emission has been detected through stacking in sub-samples with the highest H i column densities , suggesting the latter arise more likely from gas associated with galaxies at small impact parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the detected galactic counterparts to z > 2 DLAs unsurprisingly represent a biased sample; the galaxies typically have significantly higher SFRs, and on average, the metallicity of the DLAs is higher (Fynbo et al 2010;Péroux et al 2012;Fumagalli et al 2015) Fumagalli et al (2015) recently reviewed the published results and found that only 11 z > 1.9, log(N HI ) > 20.3 absorption systems were known to have galactic counterparts at the same spectroscopically identified redshift (Møller & Warren 1993;Møller et al 2002Møller et al , 2004Weatherley et al 2005;Fynbo et al 2010Fynbo et al , 2011Bouché et al 2012;Krogager et al 2012;Noterdaeme et al 2012b;Péroux et al 2013;Bouché et al 2013;Jorgenson & Wolfe 2014). Since 2015, at least five additional plausible host galaxies have been identified (Hartoog et al 2015;Srianand et al 2016;Neeleman et al 2017). In addition to these, a handful of high-z sub-DLAs with 19.0 < log(N HI ) < 20.3 have identified nearby galaxies (c.f.…”
Section: Introductionmentioning
confidence: 99%